Cover Feature: Multi‐Redox Active Carbons and Hydrocarbons: Control of their Redox Properties and Potential Applications (Chem. Rec. 9/2021). Issue 9 (18th September 2021) - Ueda, Hiroyuki; Yoshimoto, Soichiro
Abstract : The cover feature shows the structures of some multi‐redox active C x H y  molecules ( x  ≥1,   y  ≥0) and a representative cyclic voltammogram, and possible applications of such molecules. If controlled, the redox properties of such carbon and hydrocarbon molecules make them attractive candidates for organic batteries, multielectrochromic devices, and information storage devices. In all, 185 multi‐redox active C x H y  molecules mainly reported in the last decade are classified based on their chemical structures, and their redox properties as solutes and adsorbed species, which underpin the development of organic electronic devices, are summarized. See the Personal Account by H. Ueda and S. Yoshimoto (DOI: 10.1002/tcr.202100088 ).